Comparative Evaluation of Wound Healing Effect of Cord Blood Low Molecular Weight Fraction (Below 5 kDa) and Actovegin Drug in Skin Cryolesions - Gulevsky, Oleksandr; Moisieieva, Nataliia; Gorina, Olga; Akhatova, Yuliya (Problems of Cryobiology and Cryomedicine, 2021)
This paper presents the results of comparative studies of the impact of the low molecular weight (below 5 kDa) cattle cord blood fraction (CBF) and the comparator drug Actovegin on tissue regeneration after skin cryoablation in rats. Here, a local contact cryoexposure was shown to result not only in destruction of all skin layers, but secondary ischemic damage to deeper and adjacent tissues as well. The use of an injection solution of CBF as a therapy for simulated cryolesion proved its pronounced wound healing effect, manifested in accelerated reparation, improved trophicity in an injured area due to hypervascularization and prevention of sclerotic processes. The introduction of CBF and Actovegin to rats accelerated the normalization of clinical blood parameters (RBC and WBC counts, alkaline phosphatase activity) in shorter terms as compared with the control. The obtained effect may be compared with Actovegin action. Probl Cryobiol Cryomed 2021; 31(2): 116–126